2002
DOI: 10.1111/j.1574-6941.2002.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of bacterial populations in the ileum of broiler chickens and comparison with bacteria in the cecum

Abstract: Bacterial populations in the ileum of broiler chickens were analyzed by molecular analysis of 16S rRNA genes and compared to those in the cecum. Bacteria found in the ileal mucosa were mainly Gram-positive with low G+C content. There were 15 molecular species among 51 cloned sequences. More than 70% of the cloned sequences were related to lactobacilli and Enterococcus cecorum. Two sequences had 95% or less homology to existing database sequences. Terminal restriction fragment length polymorphism (T-RFLP) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
83
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(103 citation statements)
references
References 26 publications
10
83
2
Order By: Relevance
“…In addition, it has been demonstrated that T-RFLP analysis is useful for assessment of the diversity of the human fecal microbiota and rapid comparison of the community structure among individuals (13,32). T-RFLP analysis revealed differences among bacterial populations present in mucosa and lumen of the chicken ileum and cecum (8,9).…”
mentioning
confidence: 99%
“…In addition, it has been demonstrated that T-RFLP analysis is useful for assessment of the diversity of the human fecal microbiota and rapid comparison of the community structure among individuals (13,32). T-RFLP analysis revealed differences among bacterial populations present in mucosa and lumen of the chicken ileum and cecum (8,9).…”
mentioning
confidence: 99%
“…It is known that the gut microflora cans significantly be influenced by the diets and other factors, such as the hosts and environment. Therefore, the data presented in this study should be considered to be case-specific (Gong et al, 2002). The present study has also revealed the heterogeneity of Clostridium sp.…”
Section: Discussionmentioning
confidence: 74%
“…The function of the ileum (the lower end of the small intestine) is mainly nutrient absorption, while the cecum is the site where extensive bacterial fermentation occurs, resulting in further nutrient absorption and detoxification of substances that are harmful to the host (Csordas, 1995). Since these segments function differently and provide different environments, it is expected that different types of bacteria would colonize them and distinct microflora would develop (Gong et al, 2002). In this study, some differences of the Clostridium sp.…”
Section: Discussionmentioning
confidence: 88%
“…Given that the mucosa-associated microbiota has been known to play a role in pathogen control and immune modulation (Gong et al, 2002), future studies should be targeting on analyzing the mucosa-associated bacteria in relation to the responses to dietary antimicrobials. observed.…”
Section: Effect Of Antimicrobials On Gut Microbiota Communitymentioning
confidence: 99%
“…Gong et al (2002) analyzed microbiota community on the mucosa and digesta of the ileum by T-RFLP with restriction enzymes such as AluI, HhaI, and MspI and found the heterogeneous bacterial population in the mucosa and digesta in the ileum.…”
Section: Effect Of Antimicrobials On Gut Microbiota Communitymentioning
confidence: 99%